Perilaku Memaafkan pada Anak dengan Conduct Disorder - Resnia Novitasari; Amitya Kumara (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2009)
This research was aimed to explore the behavior changes, especially the forgiving behavior in children with conduct disorder. It was assumed that forgiving behavior played as predisposition in reducing destructive behavior. A training module was created and implemented to facilitate the occurrence of behavioral changes. Data was collected using Triangulation method and then analyzed with successive approximation (Neuman, 2000). There are significant changes in most of the respondents in understanding and re-experiencing the targeted behavior even though the mode of changes was vary for each subject. Forgiving behavior in children with conduct disorderwould emerge after expressing the same destructive behavior that other did to the respondent and with full support from peers.Keywords: Children with conduct disorder, forgiving behavior